1982
DOI: 10.1111/j.1651-2227.1982.tb09555.x
|View full text |Cite
|
Sign up to set email alerts
|

The Amount of Milk Consumed by 1‐3 Months Old Breast‐ or Bottle‐fed Infants

Abstract: The consumption of breastmilk was studied by the weighing method in 75 infants aged 1, 2 and 3 months (+/- 1 week), 25 infants in each group. Similarly the same number of infants in the same age groups, bottle-red ad libitum, was studied and the consumption and consumption pattern were compared between the two groups. The mean and range of consumed amounts of both types of milk were similar to that found in other studies. The means for breastmilk were 656-773-776 g and for breastmilk substitutes 713-811-853 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…The data of Hofvander et al (17) for male breast-fed infants within 1 wk of ages 1, 2, and 3 mo were 663, 791, and 81 1 g/d, respectively-intakes quite similar to those reported in Table 2. However, considerably greater intakes have been reported by Nommsen et al (1 8).…”
Section: Model O F Breast-fed Infantsupporting
confidence: 73%
“…The data of Hofvander et al (17) for male breast-fed infants within 1 wk of ages 1, 2, and 3 mo were 663, 791, and 81 1 g/d, respectively-intakes quite similar to those reported in Table 2. However, considerably greater intakes have been reported by Nommsen et al (1 8).…”
Section: Model O F Breast-fed Infantsupporting
confidence: 73%
“…Differences in pre-and postfeeding weights give the total amount of milk consumed. Test weighing is regarded as reasonably accurate (Hofvander et al, 1982;Neville et al, 1988). Validation studies suggest that actual intake may be underestimated by approximately 5%, due in part to insensible water loss (primarily from evaporation), estimated at 1-5% of measured milk intake (Brown et al, 1982;Butte et al, 1984;Woolridge et al, 1985;Dewey et al, 1991b).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The 6-month data (mean7SD, 100719 g/kg d) are excluded from the AAP Dataset, since unspecified infants in this group received solid food as early as 4 months. Hofvander et al (1982) measured milk intake of 75 exclusively breast-fed infants at ages 30, 60, and 90 (77) days (25 infants at each age). Intakes were measured over a 24-h period.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…For infants between birth and six months, IOM (1998) derived an AI for niacin based on the estimated niacin concentration of breast milk of 1.8 mg/L (Ford et al, 1983) and the reported mean intake of breast milk for this age group of 0.78 L/day (Hofvander et al, 1982;Butte et al, 1984;Chandra, 1984;Allen et al, 1991). Because of the high rate of protein turnover and the net positive nitrogen retention in infancy, tryptophan intake was not considered.…”
Section: Infants and Childrenmentioning
confidence: 99%